Energy balance of the local system of fattening bovine production in Tecpat?n, Chiapas, M?xico - Guevara, Francisco; Rodr?guez, L. A.; Saraoz, V.; La O, M.; G?mez, H.; Pinto, R.; Fonseca, Mar?a; Ruiz, B.; Nahed, J. (Cuban Journal of Agricultural Science, 2013)
The energy balance of two systems of fattening cattle production in Tecpat?n, Chiapas, M?xico is described. It is shown that the studied animal husbandry systems, which purpose is meat production, are energetically efficient with values of 4.53 and 4.99 MJ, produced for each unit of consumed energy for both productive units. Likewise, these systems develop an energy potential that does not fulfill the diet of a person, and its production of animal protein satisfies the requirements of six people per hectare a year. From the economical point of view, the animal husbandry systems of meat production have a benefit/cost relation of 1.56 Mexican pesos per each invested peso, which indicates this practice is economically possible for the producers from the area of study. Key words: animal husbandry, energy analysis, approaching methodology